2016
DOI: 10.1016/j.cmi.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak investigation for toxigenic Corynebacterium diphtheriae wound infections in refugees from Northeast Africa and Syria in Switzerland and Germany by whole genome sequencing

Abstract: Toxigenic Corynebacterium diphtheriae is an important and potentially fatal threat to patients and public health. During the current dramatic influx of refugees into Europe, our objective was to use whole genome sequencing for the characterization of a suspected outbreak of C. diphtheriae wound infections among refugees. After conventional culture, we identified C. diphtheriae using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) and investigated toxigenicity by PCR. Whole genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
2
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 41 publications
4
88
2
2
Order By: Relevance
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that diseases that can be prevented by vaccination cause flare-ups in reception and holding centers [39,42,43,44,45,46,47,48]. Outbreaks are generally more severe in refugee camps [48].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
“…Children and the elderly are undoubtedly particularly vulnerable [50,51,52]. In addition, overcrowding in holding/detention centers or refugee camps may contribute to the rapid spread of communicable diseases, such as influenza, varicella, tuberculosis, measles, and meningococcal disease [16,17,39,42,43,44,45,46,47,48,49]. It is predicted that the complication rates for influenza in this setting will be double those in the general population [53].…”
Section: Health Problems Facing Refugeesmentioning
confidence: 99%
See 2 more Smart Citations
“…All these measures would produce a big reduction in the number of infected people. What is more, controlling the epidemic is not only important for the places where the refugees are, since some cases of cutaneous diphtheria have already been reported in Denmark, Germany and Sweden, see [10], [11] We present our results in Section 3. In section 4 are exposed our conclusions.…”
Section: Introductionmentioning
confidence: 98%